A nanophotonic laser on a graph - Michele Gaio (Nature Portfolio, 2019)
The modes of random lasers, by their very nature, are difficult to design and control. Here, Gaio, Saxena et al. demonstrate a laser based on a nanophotonic network, instead of random scatterers, which allows tailoring of the optical properties and the lasing output via the network topology.